DENTAL AND ORAL HEALTH COUNSELING, DENTAL EXAMINATION AND PROVISION OF TAF FOR CARIES PREVENTION IN ELEMENTARY SCHOOL CHILDREN IN THE CONTEXT OF NATIONAL DENTAL HEALTH MONTH 202 - Kusumastiti, Anisa Ramadhani; Joestandari, Florentina; Adining Tias, Richa Rochmani; Putri, Annisa; Ardiwirastuti, Ilvana (Journal of Community Engagement and Empowerment, 2025)
Background: This community service activity was carried out in order to support the 2023 National Dental Health Month). This program includes three main activities, namely dental and oral health education, dental examinations, and provision of anti-fluoride tablets (TAF) as a preventive measure for dental caries. Objective: Counseling is carried out to increase students' knowledge and awareness of the importance of maintaining dental and oral health, including education on correct tooth brushing techniques and healthy eating patterns. Dental examinations and provision of TAF aim to detect dental and oral problems early on and as a preventive effort to strengthen teeth and prevent caries. This activity involved students from Elementary Schools in the Kediri City area. Method: Counseling is carried out using posters and tooth models, then participants are invited to brush their teeth together using the techniques that have been taught, then participants' teeth are examined and TAF is applied at the RSGM IIK Bhakti Wiyata. Results: shows an increase in students' understanding of dental and oral health, there are dental problems in most participants, and high enthusiasm for prevention using TAF. This program is expected to be a sustainable model to support promotive and preventive efforts of dental health in school-age children.